Enlightenment from Digital Transformation of International Investment banks Evidence from Morgan Stanley’s acquisition of E*TRADE - Zhao, Renhao (Transactions on Economics, Business and Management Research, 2024)
After the subprime mortgage crisis in 2008, under the circumstances of great competition pressure in the industry and slowing growth of customer assets, international investment banks gradually shifted their strategic focus to wealth management and actively sought new ways to acquire customers. Thus, digital transformation is the transformation trend at this stage. Therefore, this study provides suggestions and inspiration for the digital transformation of international investment banks through the analysis of Morgan Stanley’s strategic acquisition of E*TRADE. The study evaluates whether the acquisition is successful by analyzing financial data, strategic positioning and stock price. The results show that driven by the integration of E*TRADE’s digital platform and customer base, Morgan Stanley’s revenue and operating efficiency have improved after the acquisition, and its overall performance has also improved. The acquisition can be regarded as a success. However, through the analysis of this acquisition, it is also found that when conducting mergers and acquisitions, attention should be paid to business integration and corporate culture integration. Besides, clear corporate development goals and directions should be set to expand business boundaries and provide more comprehensive and diversified financial services, so that the acquisition activities can play their maximum benefits and better achieve corporate goals.